Determinants of menstrual hygiene among school going adolescent girls in urban areas of Hyderabad - Chajhlana, Sunil Pal Singh; Amaravadhi, Sai Ram; Mazodi, Sai Deepika; Kolusu, Venkata Sravani (International Journal Of Community Medicine And Public Health, 2019)
Background: The word adolescent is derived from the Latin word “adolescere”, which means to grow into maturity. The adolescent girls get debarred due to various social misconceptions, lack of privacy, illiteracy of parents, especially mother, low socioeconomic conditions, and lack of proper health awareness and education about this sensitive issue which ultimately results this age group into vulnerability to reproductive tract infections, which can be reduced by improving the knowledge about the menstrual hygiene. Methods: A cross sectional study was conducted among school going adolescent girls during the month of November 2018. Data was collected using a questionnaire which includes socio-demographic variables and menstrual hygiene practices. Sample size of the study was 69 students. The assessment of knowledge was done as good knowledge (score: >5/10) poor knowledge (score <5/10). The of data and the. All the data collected was entered and analysed with MS excel software 2007. Results: 28.1% girls were aware of menstruation prior to attainment of menarche.. Major source of information about menstruation is mother (53.6%). More than 80% of adolescent girls are using sanitary pads as an absorbent. Lack of disposal facility and lack of water supply are reasons for school absenteeism. Conclusions: In this study the knowledge of menstruation hygiene among the study population is significantly associated with mother’s education and occupation.